SAT0247 Efficacy and safety of modified-release prednisone in managing moderate activity systemic lupus erythematous during pregnancy: an implemented case-control study. (15th June 2017) - Meroni, M; Ramoni, V; Limonta, M; Cutolo, M
Abstract : Background: Systemic lupus erythematosus (SLE) primarily affects women of childbearing age. Despite the overall favorable outcome, pregnancy represents a challenge for both patients and clinicians. Since the complications rate is linked to the disease activity, the achievement of remission is recommended before pregnancy. Prednisone represents a cornerstone in SLE management and is safely used, at low doses (<7.5 mg daily), during pregnancy. Modified-release prednisone (MRP) optimize corticosteroid treatment strategy in rheumatic diseases, thanks to its capability of respect the physiological cortisol circadian secretion. MRP has been approved from FDA in SLE treatment, but no data are available regarding its administration during pregnancy. Objectives: We aimed to investigate whether this drug is safe and effective as the immediate release prednisone (IRP) in SLE pregnant patients. Methods: We retrospectively evaluated 9 female patients, fulfilling the ACR criteria for SLE, consulting our Centers in a 4-years observational range. All of them, thanks to a stable disease (not requiring treatment regimen modifications within 12 months), experienced a successful pregnancy during the observation. All the cases were taking low-dose MRP (5 to 7.5 mg/daily) as a baseline treatment, from at least 6 months. They were matched to 9 controls, defined as SLE patients with the same age and duration of disease, taking the same prednisone dose, from at least 6 months, in the IR formulation. Overall pregnancy outcome features; SLE disease activity (calculated at least once during pregnancy, SLEPDAI) and at baseline/post-partum (SLEDAI) score; patient's global assessment (VAS) at baseline, during pregnancy and in postpartum (mm); need of treatment changes throughout pregnancy and at postpartum (%) were assessed. Homogeneity tests, percentages and scores comparison were run out by non-parametric statistical analysis. Results: Mean MRP age group was 26±7; disease duration, 4±8 years; IR one, respectively, 28±6 and 3±9 (both, p=ns). SLEDAI at baseline was 1±0.1 among MPR and 1±0.3 among IR women; SLEPDAI, 1±0.9 and 2±0.2 (both, p=ns). No major perinatal complications were detected. Preterm births, cesarean section rates, newborns weight and APGAR scores did not differ between the two subpopulations (all, p=ns). SLEDAI assessed at postpartum was 2.8±0.6 in MRP subjects and 3.4±0.4 in IR (p<0.05). Patients VAS (MRP vs IR) was 3±0.4 and 2±09 at baseline (p=ns); 2±0.6 and 4±0.7 during pregnancy (p<0.05) and 3±0.3 and 4±0.9 at postpartum (p<0.05). Regarding treatment regimen changes (add-on strategy), the observed rates involved 1/9 (MRP) and 5/9 (IR) women during the observational gap (pregnancy+postpartum) (p<0.001). Results synthesis is reported in Table I. Conclusions: Activity (SLEDAI) score was significantly higher at postpartum and treatment had to be increased in IR patients, in comparison to the MRP, to manage SLE. VAS, conversely, was significantly higher among IR, both during pregnancy and postpartum. No major perinatal side effects were observed during the study; minor and expected complications rates did not differ between the two subpopulations. Despite the limited number of subjects, MRP treatment seems to be as safe, but more effective, in comparison to the standard IR one, during pregnancy of SLE-affected women. Disclosure of Interest: None declared